A study on incidence of pelvic floor dysfunction among non-medical professional women working in saveetha university - G.DEEPTHI; KISHOREMOY DAS; P.SANKARAKUMARAN (International Journal of Pharma and Bio Sciences, 2018)
Pelvic Floor Dysfunction is associated with network of symptoms, it comprises of pelvic organ prolapse, fecal or urinary incontinence and sexual dysfunction. Symptoms include pelvic pain, pressure, dyspareunia, incontinence, incomplete emptying. Tissues surrounding the pelvic organs may have increased or decreased sensitivity resulting in pelvic pain. The condition affects up to 50% of women. Pelvic floor dysfunction is due to the dysfunction of pelvic floor muscles, ligaments, and tissues that act like a hammock to support the organs of the pelvis: (the uterus, vagina, bladder, urethra, and rectum). It is believed that the Indian based women will not bring out these kinds of issues to the physician because of their cultural background. The women who have knowledge about these signs and the seriousness will approach physicians for further management. Those women are mostly from medical or paramedical background or some may get to know through their friends or siblings. This study aims to evaluate the level of risk for pelvic floor dysfunction among the non-medical profession middle aged women in Saveetha University. This observational study was carried out in Saveetha Engineering College, Saveetha School of Engineering, Saveetha School of Law, Saveetha School of Management. Based on inclusion and exclusion criteria, the subjects were selected, PFD - self-administered questionnaire was given and the outcome was measured. The percentage calculation was done to find out the high risk and low risk for pelvic floor dysfunction. 20% of the evaluated middle aged non-medical professional women in Saveetha University has high risk for pelvic floor dysfunction and 73% has low risk for pelvic floor dysfunction. This survey was conducted with small sample size, hence the results cannot be generalised. Since the participants are belonging to non- medical profession, they might be unaware of these issues which they had neglected in the early stages and now they are at risk for pelvic floor dysfunction. The occurrence of pelvic floor dysfunctions suggested that physicians seeing women seeking care for one condition should inquire about symptoms of other disorders also.